CANNABIDIOL IN THE MANAGEMENT OF PAIN ASSOCIATED WITH TEMPOROMANDIBULAR DISORDERS - Knipp, Andréia de Carvalho; Cunha, Vivian Rabelo; Reis, Maria Luiza Gomes; Silva, Raphaella Aparecida; Ribeiro, Rafaela Timóteo de Souza; Santos, Marcela Oliveira; de Barros, Maria Eduarda Ricardo; Costa, Patrícia de Hollanda Cavalcanti Aragão; Almeida, Monica Marletti; da Silva, João Carlos; Borges, Kayole Alves Landim; Ramos, Tânia Aparecida Oliveira; et al. (Seven Editora, 2026)
Temporomandibular disorder (TMD) comprises a group of conditions affecting the temporomandibular joint and associated structures, representing one of the main causes of non-odontogenic orofacial pain. Given the limitations of conventional therapeutic approaches, cannabidiol (CBD) has emerged as a potential alternative for pain management due to its analgesic, anti-inflammatory, and endocannabinoid system-modulating properties. This study aimed to critically analyze the scientific evidence regarding the use of cannabidiol in the management of pain associated with TMD. This is a narrative literature review with a qualitative approach, conducted in the PubMed, SciELO, and ScienceDirect databases, including publications from 2015 to 2025. Clinical studies, reviews, and experimental research addressing the use of CBD in orofacial pain, myofascial pain, or TMD were included. The findings revealed a predominance of indirect evidence, including reviews and experimental models, with a limited number of randomized clinical trials. Two recent clinical studies demonstrated significant reductions in pain and muscle activity in TMD patients treated with cannabidiol. Additionally, preclinical evidence supports the analgesic and anti-inflammatory effects of CBD, reinforcing its biological plausibility. However, methodological heterogeneity and the scarcity of robust clinical evidence limit the generalization of the findings. It is concluded that cannabidiol presents therapeutic potential in managing pain associated with TMD, particularly of muscular origin, although further clinical studies are required to establish its efficacy, safety, and clinical applicability.